Self-Medication Behavior among Breastfeeding Mothers - Nila Rusdi Rahayu; Oon Fatonah Akbarini; Eny Indriyani; Dwi Larasati (CV. Global Health Science Group, 2026)
Self-medication is a common practice among breastfeeding mothers and may pose risks to infants due to potential drug exposure through breast milk. Limited awareness of medication safety and the widespread availability of over-the-counter drugs contribute to this behavior. This study aimed to describe self-medication behavior among breastfeeding mothers. A descriptive cross-sectional study was conducted involving 120 breastfeeding mothers with infants aged 0–24 months. Data were collected using a validated and reliable self-administered online questionnaire. The instrument consisted of 25 items covering self-medication practices, including types of medications used, frequency, reasons for use, sources of information, and awareness of medication safety. Data were analysed using descriptive statistics. Self-medication was reported by 78.3% of respondents. Analgesics and antipyretics were the most commonly used medications, followed by cold remedies and vitamins. The main reasons for self-medication were perceived mild symptoms, prior experience, and convenience. Most respondents relied on informal sources of information, particularly the internet and social media. Awareness of medication safety during breastfeeding varied, with a substantial proportion demonstrating moderate to poor understanding. Conclusions: Self-medication behaviour is prevalent among breastfeeding mothers and is influenced by accessibility, prior experience, and reliance on non-professional information sources. Limited awareness of medication safety highlights the need for improved health education and professional guidance to support safer medication practices during breastfeeding.